(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Ischemia-reperfusion injury (IRI) to the liver causes inflammatory and oxidative stress events, as well as hepatocyte apoptosis and liver injury. In this study, we investigated whether infliximab, DMF, and their combination reduced ROS production in rat livers and played a protective role in the pathogenesis of I/R-induced liver injury in rats.Aim: study the role of infliximab, DMF, and their combination in hepatic I/R injury. Methods: 5 groups of 40 male rats were randomized in the following groups: G1; sham: G2 control; ischemia-reperfusion (I/R): Rats were subjected 60-minute ischemia then 90-minute reperfusion., G3: I/R+IFX (I/R+IFX peritoneally administration of 7 mg/kg body weight 72 hrs. before I/R), G4; I/R+DMF (I/R+DMF peritoneally at a dose of 30 mg/kg body weight on 72 hrs. before I/R), and G5; I/R + Comb (IFX peritoneally 7 mg/kg +DMF 30 mg/kg body weight).Results: Infliximab, DMF pre-treatment (7 g/kg, 30 mg/kg body weight, respectively), and their combination for 3 days before ischemia lowered ALT, AST, and TNF-α in the rat liver, while elevated GSH-Px level, and reduced liver injury. Pretreatment with the same combination dramatically lowered ALT, AST, and TNF-α and increased the level of GSH-Px.Conclusion: Infliximab is a powerful TNF-α blocker and DMF is a master oxidative stress regulator. Both drugs limit ROS release and cell death signaling which protects the hepatocytes from injury during liver ischemia reperfusion.